Increased structural connectivity of thalamic stimulation sites to motor cortex relates to tremor suppression - Riskin-Jones, Hannah H. (Neuroimage Clin, 2021)
Deep brain stimulation (DBS) of the ventral intermediate nucleus (VIM-DBS) is a highly successful treatment for medication-refractory essential tremor (ET). Clinical outcomes are dependent on accurate targeting. Here, we aim to develop a framework for connectivity-guided DBS targeting by evaluating probabilistic tractography and clinical response at both initial programming (IP) and clinical follow-up (CF). Magnetic resonance imaging and clinical outcomes were evaluated in 23 ET patients who were treated by VIM-DBS at the University of California Los Angeles (20 at IP, 18 at CF, 14 at both). Lead-DBS was used to model the volume of tissue activated tissue (VTA) based on programming configurations at both IP and CF. Probabilistic tractography, calculated in FSL, was used to evaluate 1) clinically weighted whole brain connectivity of VTA; 2) connectivity between VTA and freesurfer-derived target regions of interest (ROI) including primary motor, premotor, and prefrontal cortices, and cerebellum; and 3) volume of intersection between VTA and probabilistic tractography-based segmentation of the thalamus. At IP, individual contacts were scored as high or low efficacy based on acute tremor improvement. At CF, clinical response was measured by percent of change of the Clinical Rating Scale for Tremor (CRST) compared to preoperative scores. Contributions from each target ROI to clinical response was measured using logistic regression for IP and linear regression for CF. The clinically weighted map of whole brain connectivity of VTA shows preferential connectivity to precentral gyrus and brainstem/cerebellum. The volume of intersection between VTA and thalamic segmentation map based on probabilistic connectivity to primary motor cortex was a significant predictor of contact efficacy at IP (OR = 2.26 per 100 mm(3) of overlap, p = .04) and percent change in CRST at CF (β = 14.67 per 100 mm(3) of overlap, p = .003). Targeting DBS to the area of thalamus most connected to primary motor cortex based on probabilistic tractography is associated with superior outcomes, providing a potential guide not only for lead targeting but also therapeutic programming.